Gear fault detection in gearboxes operated in non-stationary conditions based on variable sideband analysis without a tachometer - Du, Nguyen Trong; Dien, Nguyen Phong; Nga, Nguyen Thi Thanh (Frontiers in Mechanical Engineering, 2022)
Machine fault diagnostics techniques by vibration signal analysis have been applied and widely developed in the industry. In recent years, using the least number of measuring devices to simplify the diagnostic process of gear fault has attracted many researchers. Various digital signal analysis methods in the time and frequency domains have been effectively applied to detect gear faults of gearboxes operated in stationary conditions or rotational speeds with minor fluctuations. But in reality, gearboxes often work at rotational speeds with large fluctuations and variable loads due to technological progress. In such cases, the measured vibration signal is the amplitude-frequency modulated signal. Therefore, the traditional vibration analysis methods have become ineffective. The modulated signal analysis techniques often require additional key-phase information measured by a tachometer to achieve good diagnostic results. However, setting up the tachometer while operating the machine is not effortless. This paper offers a new approach combining many methods to detect gear faults based on sideband analysis in the time-frequency distribution of measured vibration signals using only a single measurement channel. This study is applied in many cases where the machine cannot stop and reduce instrumentation requirements and can develop to build an online diagnostic system.